2017
DOI: 10.3390/genes8030090
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Sampling of Escherichia coli After Changing Oxygen Conditions Reveals Transcriptional Dynamics

Abstract: Escherichia coli is able to shift between anaerobic and aerobic metabolism by adapting its gene expression, e.g., of metabolic genes, to the new environment. The dynamics of gene expression that result from environmental shifts are limited, amongst others, by the time needed for regulation and transcription elongation. In this study, we examined gene expression dynamics after an anaerobic-to-aerobic shift on a short time scale (0.5, 1, 2, 5, and 10 min) by RNA sequencing with emphasis on delay times and transc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 75 publications
(100 reference statements)
0
25
0
Order By: Relevance
“…were performed by Feuer and colleagues 26 . Briefly, E. coli K-12 strain W3110 cells were grown anaerobically in a 3-liter continuously stirred tank bioreactor at pH7 and 37°C, and stirred at 500 rpm with a Rushton turbine.…”
Section: E Coli Transcriptome-wide Expressions Follow Lognormal Distmentioning
confidence: 99%
“…were performed by Feuer and colleagues 26 . Briefly, E. coli K-12 strain W3110 cells were grown anaerobically in a 3-liter continuously stirred tank bioreactor at pH7 and 37°C, and stirred at 500 rpm with a Rushton turbine.…”
Section: E Coli Transcriptome-wide Expressions Follow Lognormal Distmentioning
confidence: 99%
“…In the corn soil experiment, the drying and re-wetting treatments lasts three and six days, respectively, while the phytohormone treatments lasted only 24 hours, and in the bean soil experiment, treatments were continuously applied for the approximately five weeks of the experiment. Given that differential transcription of RNA can occur within 30 seconds after an environmental stimulus (33) but cell doubling takes considerably longer (~10 minutes for only the very fastest-growing strains under optimal laboratory conditions (34), and many hours for others especially in natural environmental conditions (35 and references therein)), the 16S ratio method may be more sensitive in short time-frames than the CTC staining method. This may explain why the relatively short (24-hour) phytohormone treatments in corn soil resulted in relatively large decreases in percent activity using 16S ratios (average difference of 17.8% activity compared to ‘post-water’), but much smaller (albeit significant) increases in percent activity using CTC staining (average difference of 5.1% activity compared to ‘post-water’) (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In these early studies, Gluconobacter oxydans was cycled between zones with low and high oxygen availability to study the effect on gluconic acid production. More recent studies used similar approaches to study the effect of oxygen availability on intracellular processes in E. coli and C. glutamicum [18,[33][34][35][36]. In these studies, transcriptional changes between aerobic and anaerobic environments explained observed alterations in stoichiometry and kinetics, as well as production of ethanol and organic acids, indicating that E. coli responds rapidly to dissolved oxygen gradients [33].…”
Section: Gas Mixingmentioning
confidence: 99%